Methodical instructions for laboratory work on the discipline "Building constructions" for students of the educational direction 192 "Construction and Civil Engineering" : calculation of building structures for strength, rigidity and fire resistance - Fesenko, Оleh Аnatoliyovych; Dmitrenko, Yevhen Anatoliyovych (NULES of Ukraine, 2020)
Methodical instructions contain examples of calculation of building structures for strength, rigidity and fire resistance.
Recommended by the Academic Council of the Faculty of Construction and Design of the National University of Life and Environmental Sciences of Ukraine (Protocol № __3__ of October 20, 2020).
Keywords: будівельна справа; будівництво